Analysis of Students Learning Ethics in Online Learning via Zoom in Mathematical Communication Ability at Senior High School Bunda Kandung Jakarta - Nuary, Rusdi Hamdany (Journal of Instructional Mathematics, 2022)
This research is based on the results of observations of class X IIS regarding student's mathematical communication in online learning ethics via zoom. Initial findings indicate that mathematical communication skills have emerged but are not optimal. In general, the research objective is analyzing student’s online learning ethics via Zoom in mathematical communication. The method used is descriptive qualitative method to reveal facts. The data are collected through observation, interviews, documentation and triangulation/combination. This study involved three students from class X IIS and the teacher as a validator at Senior High School Bunda Kandung. The data analysis technique uses an interactive model through four stages, which are data collection, data reduction, data display, and drawing conclusions/ verification. The results showed that student's learning ethics via zoom on student's mathematical communication skills for subjects 1 and 2 were optimal because subjects 1 and 2 were able to communicate, express ideas, manage thoughts, analyze and evaluate mathematical thoughts. However, subject 3 has not been optimal in communicating their mathematical thoughts coherently and clearly. Subject 3 is unable to analyze his thoughts and unable to behave well with his friends.